A case of cerebral hypoplasia/dysplasia detected at autopsy - İnanir, Nursel Türkmen; Eren, Filiz; Ural, Mustafa Numan; Eren, Bülent; Gürses, Murat Serdar (Soudni lekarstvi, 2015)
UNLABELLED: Presented case was a 2-year-old baby girl who had been treated for nearly one year with the indication of multifocal epileptiform anomaly. She was found dead in her bed in morning hours, autopsy was planned after prosecutors investigation. On internal autopsy examination, shrinkage of gyral structures in the frontal, and parietal lobes of the left hemisphere, markedly enlarged sulci, and a hypoplastic appearance were noted. Histopathological examination revealed evidence of pneumonia, brain exposed microgyral formations, disordered cortical stratification, hypercellularity, dysmorphic neuronal structures, balloon cells with diagnosis of cortical dysplasia. Pneumonia was reported as a cause of death. We aimed to discuss in the light of the literature a case with cerebral hypoplasia which is rarely seen at forensic autopsies. KEYWORDS: cerebral hypoplasia/dysplasia - autopsy - congenital malformation - sudden death.
Keywords: Death, Sudden; Forensic Pathology; Cerebral Cortex; ženské pohlaví; náhlá smrt; Female; lidé; Humans; mozková kůra; pitva; soudní patologie; předškolní dítě; Autopsy; Child, Preschool